Disasters : the biggest disasters in history from salt in the Indus Valley to Hurricane Sandy - Connolly, Kieron (Scholastic, 2013)
What was the impact of Hurricane Sandy? How many people were killed in the Indian Ocean Tsunami? Why did the Titanic sink? What caused the Bhopal Chemical Blast? How long did the Little Ice Age last? And what started the Great London Fire?